Evaluation of the Antibacterial Activity of Ethanolic Extracts Obtained from Aglaonema commutatum Schott and its Cultivars Against Citrobacter freundii - Opryshko, Maryna; Tkachenko, Halyna; Buyun, Lyudmyla; Kurhaluk, Natalia; Góralczyk, Anna; Tomin, Vładimir; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
Due to the indiscriminate use of antimicrobial drugs, the emergence of human pathogenic microorganisms resistant to antibiotics has been increased. This has caused many clinical problems in the treatment of infectious diseases. Aglaonema plants have been widely used in recent years because of its anti-aging and longevity properties, natural anti-allergic and anti-inflammatory properties. There is a need to evaluate extracts of this plant in order to provide scientific proof for its wide application in the traditional medicine system. In the present study, we focused on investigating the in vitro antibacterial activity of ethanolic extracts obtained from Aglaonema commutatum Schott and its cultivars (Malay Beauty, Silver Queen, and Silver King), cultivated under glasshouse conditions at M.M. Gryshko National Botanical Garden, National Academy of Science of Ukraine against Citrobacter freundii strain locally isolated from human materials. The testing of the antibacterial activity of the plant extracts was carried out in vitro by the Kirby-Bauer disc diffusion technique. The extracts from A. commutatum and cultivars Silver Queen exhibited higher inhibitory activity (P<0.05) than the extracts from cv. Melay Beauty and cv. Silver King. The highest in vitro inhibition was scored by A. commutatum, followed by cultivats Silver Queen, Malay Beauty, and Silver King. The ethanolic extracts obtained from the leaves of Aglaonema commutatum and its cultivars (Malay Beauty, Silver Queen, and Silver King) has the potential for use as natural antimicrobial agents. Further in vivo and in vitro antimicrobial, phytochemical and toxicological studies are required to evaluate the chemotherapeutic effect of the plant.